Pena Melawan Peluru Kontribusi Surat Kabar Kedaulatan Rakyat dalam Perjuangan Kemerdekaan pada Revolusi Fisik Yogyakarta (1947-1950) - wahyudi, ilham; arif saefudin (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research discusses the strategic role of Kedaulatan Rakyat newspaper during the 1947-1950 Physical Revolution period as a propaganda tool, disseminator of independence ideology, and mobiliser of the people. Kedaulatan Rakyat functioned as the main media in disseminating information related to the independence struggle, especially in Yogyakarta, through the narrative of the victory of the Indonesian National Army (TNI) and the solidarity of the people. In addition, the newspaper played an important role in strengthening the spirit of resistance against Dutch military aggression through the narrative of anti-colonialism and nationalism in its editorial section. Despite the challenges of Dutch confiscation and limited resources, Kedaulatan Rakyat was still able to distribute information through a secret distribution network. By conveying military strategy and the success of the TNI, Kedaulatan Rakyat succeeded in mobilising the public, creating a sense of optimism, and strengthening popular support for the independence struggle. This research highlights how mass media can be an important instrument in a nation's political and military struggle.